Zoom-Mediated Online Learning Towards Students Reading Interest: An Experimental Study - Laras Aryandini Sukma; Ali Mustadi; Aninditya Sri Nugraheni (AL-ISHLAH: Jurnal Pendidikan, 2022)
In the last two years, the trend of online learning in universities has utilized Zoom as the main media to conduct the learning process. This study sought to determine the effect of using Zoom on students' reading interest. This study was conducted qualitatively using an ex-post facto design. The samples of this study (n=32) were chosen by a cluster random sampling procedure from the total population (N=65). The collected data were analyzed through simple linear regression. The results of the test and interpretation in this study revealed that the use of Zoom as an online learning medium had no significant effect on students' reading interest. The findings of this study disconfirmed a number of researchers who assumed that the students’ independence to search for information or materials online will automatically increase their reading interest. Based on the results of the analysis on the coefficient of determination, the contribution of zoom to students’ reading interest was only 18.4%. This indicated that students’ willingness to search for information independently was not motivated by a high reading interest although students had a high awareness to study independently and to search for reading sources on the internet. Factors outside the use of zoom provided a greater contribution (81.6%). The implication of this study was the need to evaluate the use of zoom as an online learning medium to increase students' reading interest.